Revealing the structure of high-water content biopolymer networks: Diminishing freezing artefacts in cryo-SEM images. (December 2017) - Efthymiou, Christina; Williams, Martin A.K.; McGrath, Kathryn M.
Abstract: High-water content biopolymer gels are widely used in diverse areas of research and in many commercial processes, including a significant proportion of importance to the food and pharmaceutical industries. The internal structures of these hydrogels are complex and span many length scales, the specifics of which are important in determining functionality. Elucidating these structures is critically important in extending and tailoring their use. Cryo-scanning electron microscopy (cryo-SEM) is a popular method for structural elucidation. A critical step in this imaging technique is cryo-fixation. However, consideration of the literature reveals that images of inefficiently cryo-fixed networks remain widely reported as being representative of the native structure of gels despite being significantly damaged by ice formation. Here, we show that the application of slow freezing methods, like the very commonly used slushy nitrogen method, indeed yield erroneous structures and produce singularly common structures for both protein and polysaccharide hydrogels. On the contrary, we demonstrate, by rapidly freezing thin samples of low concentration protein amyloid fibril hydrogels using a propane jet freezer, that cryo-SEM imaging of biopolymer hydrogels in their native state is feasible. In contrast, while the use of cryo-protectants is successful in reducing ice crystallisation, it can affect the bonding within hydrogels and hence, modify the structure under examination. Graphical abstract: Highlights: A mechanism describing the formation of freezing artefacts during cryo-fixation for cryo-SEM imaging is proposed. Cryo-SEM imaging of the native state of high-water content biomaterials is feasible using propane jet freezer. The use of cryo-protectants in cryo-SEM alters the native architecture of biopolymers. The faster the eutectic point is reached, the fewer artefacts are introduced upon freezing. The thinner the sample and the faster the freezing rate, the easier sample vitrification is achieved.